2008
DOI: 10.1038/ijo.2008.256
|View full text |Cite
|
Sign up to set email alerts
|

Weight-loss maintenance in successful weight losers: surgical vs non-surgical methods

Abstract: Objective Since large weight losses are rarely achieved through any method except bariatric surgery, there have been no studies comparing individuals who initially lost large amounts of weight through bariatric surgery or non-surgical means. The National Weight Control Registry (NWCR) provides a resource for making such unique comparisons. This study compared amount of weight regain, behaviors, and psychological characteristics in NWCR participants who were equally successful in losing and maintaining large am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
102
0
12

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(116 citation statements)
references
References 52 publications
2
102
0
12
Order By: Relevance
“…Indeed, only one study to date has assessed whether aerobic exercise is even a feasible therapeutic option in this patient population (20). Case-controlled studies indicate that bariatric surgery patients have lower levels of physical activity than weight-matched nonsurgery controls (21)(22)(23). A number of retrospective cohort studies report a positive association between physical activity and postsurgery weight loss (24)(25)(26)(27)(28).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, only one study to date has assessed whether aerobic exercise is even a feasible therapeutic option in this patient population (20). Case-controlled studies indicate that bariatric surgery patients have lower levels of physical activity than weight-matched nonsurgery controls (21)(22)(23). A number of retrospective cohort studies report a positive association between physical activity and postsurgery weight loss (24)(25)(26)(27)(28).…”
Section: Resultsmentioning
confidence: 99%
“…Case-control studies report significantly lower levels of physical activity than weight-matched nonsurgery controls (21)(22)(23). Indeed, it is not clear whether an exercise training intervention is even a feasible therapeutic option in this unique patient population.…”
Section: Discussionmentioning
confidence: 99%
“…Clinicians can promote long-term maintenance of weight loss using the strategies presented in Box 4. [39][40][41][42] To complete this intervention, a sixth "A" should be added to the mnemonic: advocate -that is, to advocate for environmental and policy changes that support healthy eating and physical activity.…”
Section: Unanswered Questionsmentioning
confidence: 99%
“…These finding are consistent with other WLS studies that report, in most cases of recidivism, weight loss failure is due to dietary noncompliance or an inability to change eating and exercise behaviors. [17][18][19][20][21][22] Findings from the Swedish Obesity Subjects study reported that baseline caloric intake was 2,800 calories. 35 At 6 months postsurgery, the study reported caloric intake at approximately 1,500 calories, and by 10 years postsurgery, the calorie intake had increased to an average of 1,800-2,000 calories per day.…”
Section: Discussionmentioning
confidence: 99%
“…[13][14][15][16] Many studies show that, in most cases of recidivism, weight loss failure is due to dietary noncompliance or an inability to change eating, social, and exercise behaviors. [17][18][19][20][21][22] Following WLS, individuals must learn to cope with internal and external eating behavior stimuli, including the family environment, food availability, and emotional stress that may lead to weight regain. 23 This represents the complex behavioral and environmental factors associated with weight maintenance and potential weight regain following WLS.…”
Section: Introductionmentioning
confidence: 99%